The environmental stewardship program: lessons on creating long-term agri-environment schemes - Burns, E.; Zammit, C.; Attwood, S.; Lindenmayer, D. (ANU Press, 2016)
The conservation of biodiversity on private land is both a high priority and a considerable challenge. An effective response to this challenge requires a combination of legislative and incentive mechanisms, coupled with preparedness by government to review and revise administrative arrangements. Preliminary results from the Environmental Stewardship Program, established by the Australian Government, highlight that there is a role for market-based approaches. However, implementation of this program through a Commonwealth bureaucracy was not without its challenges. Here we provide an overview of the program’s implementation from 2007 to 2012, followed by discussion of some key lessons learned.